(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the linguistic and cultural dimensions of the concept of "food" in Uzbek and Italian cultures. Through thematic analysis, discourse analysis, and a comparative approach, the research investigates the symbolic meanings, social dynamics, and linguistic expressions associated with food in these two distinct cultural contexts. The findings highlight the profound cultural significance of food as a marker of identity, social cohesion, and communication within Uzbek and Italian societies. The study contributes to a deeper understanding of how food functions as a cultural symbol and medium of social interaction in diverse cultural settings.